1980
DOI: 10.1093/brain/103.4.885
|View full text |Cite
|
Sign up to set email alerts
|

Transmission and Scanning Electron Microscopy of Spongiform Change in Creutzfeldt-Jakob Disease

Abstract: Brains from three human cases of Creutzfeldt-Jakob disease and three monkey cases of transmitted Creutzfeldt-Jakob disease were examined. Spongiform change was present in all cases on both light and electron microscopic examination. Electron microscopic examination revealed membrane alterations within vacuoles in all cases. On SEM, both ulcerated and focally thickened membranes were apparent; TEM revealed splitting of unit membranes as well as focally thickened amorphous membranes. Small blisters with 70 to 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The vacuoles observed by light microscopy represent focal swellings of axonal and dendritic neuronal processes associated with the loss of synaptic organelles, and accumulation of abnormal membranes by electron microscopy. [22][23][24] They may be distributed throughout the gray and white matter but are generally most prominent in the gray matter neuropil. They typically range in size from 5 to 25 μm but in advanced cases they may be as large as 100 μm.…”
Section: Pathologic Features Of Prion Diseasesmentioning
confidence: 99%
“…The vacuoles observed by light microscopy represent focal swellings of axonal and dendritic neuronal processes associated with the loss of synaptic organelles, and accumulation of abnormal membranes by electron microscopy. [22][23][24] They may be distributed throughout the gray and white matter but are generally most prominent in the gray matter neuropil. They typically range in size from 5 to 25 μm but in advanced cases they may be as large as 100 μm.…”
Section: Pathologic Features Of Prion Diseasesmentioning
confidence: 99%
“…The clinical signs are confined to the central nervous system, and no immune response seems to accompany the progression of the illness [9]. The molecular basis of neurological dysfunction in prion diseases is not known, although there is evidence that spongiform degeneration and death of neurons is related to the accumulation of PrP Sc , which causes alterations in membrane receptors or ion channels functions, among other effects [12,13]. Kristensson et al [14] reported that prion infection of cultured mouse neuroblastoma cells affected intracellular Ca# + regulation, inducing abnormalities in intracellular Ca# + release from internal stores and influx of extracellular Ca# + .…”
Section: Introductionmentioning
confidence: 99%
“…J-C disease is classified as one of subacute spongiform encephalopathies. 4 These represent a group of transmissible encephalopathies caused by unknown agents considered by some observers to represent unconventional viruses. 5,6 They have a long incubation period of many months or years and a characteristic, unremitting always fatal course.…”
Section: Discussionmentioning
confidence: 99%